Communication barriers from nurses’ and elderly patients’ points of views at medical-surgical wards - Mohammadzadeh, sh; Bakhtiari, S; Bakhtiari, S; Moshtagh, Z; Moshtagh, Z; Ebrahimi, E; Ebrahimi, E (Advances in Nursing & Midwifery, 2007)
Abstract Introduction: Communication is an inevitable aspect of nursing care of patients and the elderly and an essential factor in attaining positive aspect of treatment. Removing communication barriers can have a significant role in improving quality of care in the elderly and facilitating recovery of patients. Purpose: This descriptive study was conducted to determine communication barriers from nurses’ and elderly patients’ points of views at medical-surgical wards of hospitals affiliated to Isfihan Medical University. Materials and Methods: A questionnaire completed by was used for data collection. Subjects included 110 nurses and 110 elderly patients. The nurses and patients were selected by randomization and convenience sampling methods respectively. Different statistical tests were used for data analysis. Results: Communication barriers from nurses’ points of views included tiredness of nurses (%89.8), speaking too fast (%88.9), forgetfulness and weak memory of the elderly patient (%92.6), auditory and visual disorders (%89.8), badly injured patients in the wards (%97.2) and crowdedness of the wards. The points of views in the elderly patients mostly included lack of respect to their dignity (%98.2) and lack of attention to their questions (%93.6). Conclusion: With respect to the findings, nursing authorities should pay attention to the working condition of nurses and provide facilities for them. Nurses should be supported to be able to dedicate their time and energy for effective communication. In addition, continuing education programs regarding communication skills with the elderly and regular evaluation of these programs can be helpful. Geriatric nursing education should also be integrated in the baccalaureate program of nursing. Keywords: Communication barriers, Nurse, Patient, Old person.